Venezuela in times of social, economic and political strife within TESOL affiliate grassroots advocacy initiatives: Implications for other contexts - Kara Mac Donald; Jose Franco; Orangel Abreu (English Language Teaching and Research Journal (ELTAR-J), 2020)
Settling in a new region may imply a plethora of challenges for Students with Interrupted Formal Education (SIFE) and for any migrant or immigrant, no matter their background. Such challenges are as diverse as the individuals and their nationalities. Some SIFE have common experiences as immigrants relocating to a new country of residence, regardless of the status of migration. The range of constraints and situations that impact students’ access to formal education and/or its continuity in host countries is broad and deserves our attention as teachers and researchers. In this sense, the analysis of interviews conducted with SIFE from different universities and host countries has led to the consideration of particular difficult situations such as the reasons that pushed them to interrupt their studies and how it has impacted them personally, their access to employment, language, and home country return expectations. Taking into account the value of SIFE ́s own testimony obtained by means of interviews, this article addresses some of the diverse challenges they face in their host countries to raise awareness of the similarities and differences of their experiences, to promote socio-political advocacy for their needs, and to offer ELT educators ways in which they can respond to these special learners’ needs. It also in part can inform socio-political advocacy for SIFE who remain in their home countries of origin, as they often confront similar challenges as the local, regional or national context has been altered so much that they may also be in a context without adequate support.